2020
DOI: 10.1096/fj.202000562rr
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose dietary supplementation with zinc prevents gut inflammation: Investigation of the role of metallothioneins and beyond by transcriptomic and metagenomic studies

Abstract: Although it is known that zinc has several beneficial roles in the context of gut inflammation, the underlying mechanisms have not been extensively characterized. Zinc (Zn) is known to be the primary physiological inducer of the expression of the metallothionein (MT) superfamily of small stress‐responsive proteins. The expression of MTs in various tissues is induced or enhanced (including the gastrointestinal tract (GIT)) by a variety of stimuli, including infection and inflammation. However, the MTs’ exact ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 110 publications
1
11
0
Order By: Relevance
“…Zhang et al [ 55 ] showed that zinc modified the cecal microbial community in broilers by making abundant in the populations of total bacteria, including Lactobacillus, and reducing the populations of Salmonella. Foligné et al [ 56 ] suggested that zinc supplementation provided a significant increase in endogenous Clostridiaceae in mice. Meanwhile, in a mouse steatohepatitis model, Kitagawa et al [ 27 ] have recently demonstrated that rifaximin improved ethanol-induced liver injury with drastic modification of the small intestine microbiota; they elucidated that rifaximin decreased the relative abundance of Erysipelotrichales and increased Bacteroidales.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 55 ] showed that zinc modified the cecal microbial community in broilers by making abundant in the populations of total bacteria, including Lactobacillus, and reducing the populations of Salmonella. Foligné et al [ 56 ] suggested that zinc supplementation provided a significant increase in endogenous Clostridiaceae in mice. Meanwhile, in a mouse steatohepatitis model, Kitagawa et al [ 27 ] have recently demonstrated that rifaximin improved ethanol-induced liver injury with drastic modification of the small intestine microbiota; they elucidated that rifaximin decreased the relative abundance of Erysipelotrichales and increased Bacteroidales.…”
Section: Discussionmentioning
confidence: 99%
“…Neural, immunological and hormonal pathways all offer potential mechanisms by which gut microbes may influence neurological development. Changes in gut microbial composition and resulting functional differences have been observed with differential dietary zinc intake in porcine and murine models as well as human studies [7274]. We recently described dietary zinc-induced reversal of ASD behaviours in Shank3B −/− KO mice [8, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Neural, immunological and hormonal pathways all offer potential mechanisms by which gut microbes may in uence neurological development. Changes in gut microbial composition and resulting functional differences have been observed with differential dietary zinc intake in porcine and murine models as well as human studies [72][73][74]. We recently described dietary zinc-induced reversal of ASD behaviours in Shank3B -/-KO mice [8,49].…”
Section: Discussionmentioning
confidence: 99%